The Effect of Auditor Competence and Independence on Audit Quality: The Moderating Role of Audit Fees (A Case Study of Public Accounting Firms in Bandung) - NURSAID, Manurung Miranda Lidya; ZAPUTRA, Ali Rahman Reza (PT Keberlanjutan Strategis Indonesia, 2025)
The purpose of this study is to evaluate various aspects of audit quality in Indonesia, with a particular emphasis on auditor competence, independence, and audit costs at public accounting firms in Bandung. A quantitative approach is applied using descriptive, associative, and causal methods. To collect data, auditors from 17 randomly selected public accounting firms were used as respondents in a closed-ended questionnaire based on a Likert scale. The data were analyzed using SEM-PLS techniques together with the SmartPLS 4 tool. The results of the analysis showed that auditor competence and independence greatly influence audit quality. Conversely, audit fees do not significantly affect audit quality, but they weaken the relationship between competence and audit quality. Meanwhile, audit fees do not moderate the relationship between independence and audit quality. These findings highlight the crucial role of auditor competence and objectivity in maintaining high audit quality, in line with Attribution Theory. Practically, companies should invest in improving auditor skills, ensure auditor independence, and establish audit fees that are fair and proportional. Future studies are encouraged to adopt a mixed-method approach.